Strategi Komunikasi Pemasaran Melalui Media Sosial Instagram (Studi kasus Pada Online Shop SEIWAY di Tangerang selatan) - Taufan Prahara (Cakrawala - Jurnal Humaniora, 2023)
Sales methods have developed from bartering, direct sales in stores, door to door marketing (salesmen), advertising on television and radio, entering the digital marketing era in the 2000s. Digital (online) marketing involves promoting products or services using social media technology, connecting producers directly with consumers, allowing for daily advertising, uploading product videos, and direct online sales where consumers can interact and transact via live chat on online platforms. Social media consisting of Facebook, Instagram, WhatsApp, and online markets such as Shopee, Lazada, and Tokopedia. The focus of this research is online sales via the social media platform Instagram. The research subject is Small and Medium Enterprises (MSMEs) in South Tangerang which are famous for Sei Sapi SeiWay, a new processed beef product with the taste of roast beef which is popular among young people. Researchers are interested in discussing digital marketing in SeiWay sales in South Tangerang. The aim of this research is to understand SeiWay's marketing communication strategy through the social media platform Instagram. The research methodology used is qualitative research aimed at finding insights that cannot be obtained through statistical procedures or other quantification methods. The results is SEI WAY's sales experienced an increase in sales, both sales of food products and franchises, by participating in marketing programs on Instagram social media. However, not all advertising programs on Instagram are followed due to limited budget to place advertisements every month on Instagram. The recommendation for SeiWay is hire a marketing digital team’s for increase sales via media soscial.